Red blood cell distribution width (RDW) is a significant predictor of survival in laryngeal cancer patients: systematic literature review and meta-analysis: RDW in laryngeal cancer - Nocini, Riccardo; Sanchis-Gomar, Fabian; Lippi, Giuseppe; Mattiuzzi, Camilla (Journal of Medical Biochemistry, 2023)
Background: This systematic literature review and meta-analysis investigated whether the red blood cell distribution (RDW) may predict survival outcomes in laryngeal cancer patients undergoing curative treatment.Methods: We conducted an electronic search in Medline and Scopus using the keywords “red blood cell distribution width” OR “RDW” AND “laryngeal cancer” OR “larynx cancer” OR “laryngeal carcinoma” OR “larynx carcinoma,” without time or language restrictions (up to February 2022), for identifying studies investigating the prognostic value of RDW in patients with any form of laryngeal cancer and with a primary endpoint that was set as survival rate and/or disease-free survival between 1 and 10 years after curative treatment. The research was conducted according to the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) 2020 reporting checklist.Results: The digital search enabled us to identify five studies, that were finally included in our pooled analysis (survival rate and/or disease-free survival covered a window between 2.7-8.3 years). In four of the five studies, an enhanced RDW value in laryngeal cancer patients undergoing surgical or radiation treatment was associated with poorer survival (range of odds ratio [ORs], 2.28-10.44). In the pooled analysis, increased RDW conferred an over 3-fold higher risk of dying during follow-up after curative treatment for laryngeal cancer (OR, 3.37; 95%CI, 1.41-8.10).Conclusion: RDW retains a clinically important prognostic value in patients with laryngeal cancer undergoing curative treatment. Clinicians could acknowledge this information for using a more aggressive therapy or setting narrower follow-up in laryngeal cancer patients with increased RDW values.
Keywords: RDW; red blood cell distribution width; anisocytosis; laryngeal cancer; larynx cancer